A Critical Review of Child Labour in Nigeria and The Case for Child Entrepreneurship - Mike Akpa AjaNwachuku (Universitas Muhammadiyah Sidoarjo, 2016)
Nigeria and the world over condemn forced or exploitative labour of a child, for the obvious reason of the adverse physical, psychological, mental and emotional effect of it on children. What is condemned is not child labour per se, but child forced or exploitative labour. This paper analyses the condemnable child forced or exploitative labour, distinguishes it from the accepted child labour and makes a case for the advancement from child labour to child entrepreneurship. It posits that the advancement to child entrepreneurship shall enable the Nigerian child to contribute their bit to the financial wellbeing of their family and the economic development of Nigeria.